Lagged duration dependence in mixed proportional hazard models - Matteo Picchio (Institute for the Study of Labor (IZA), 2011)
We study the non-parametric identification of a mixed proportional hazard model with lagged duration dependence when data provide multiple outcomes per individual or stratum. We show that the information conveyed by the within strata variation can be exploited to non-parametrically identify lagged duration dependence in more general models than in the literature.
urn:nbn:de:101:1-201111213160
Keywords: C14; C41; 330; lagged duration dependence; mixed proportional hazard models; identification; multiple spells; parallel data; Statistische Bestandsanalyse; Lag-Modell; Theorie